Overlying rock movement and mining pressure in a fully mechanized caving face with a large dip angle - Chen, Ying; Wang, Zhiwen; Hui, Qianjia; Zhu, Zhijie; Sun, Dequan; Chen, Yang; Zhang, Xiufeng; Wang, Zhaoyi; Wang, Jian; Zhao, Jian (Frontiers in Earth Science, 2022)
The overlying rock movement and mining pressure in the fully-mechanized caving face with a large dip angle were systematically investigated according to theoretical analysis, similar material simulation, numerical calculation and field monitoring. The following conclusion were obtained: (1) The theoretical analysis showed that the roof movement characteristics at different positions of the working face are quite different. The mining pressure in the upper section of the working face is primarily controlled by the structural instability of the main roof. The stable structure of the main roof are easily formed in the middle and lower sections of the working face, and the mining pressure is mostly controlled by the collapse of the immediate roof. (2) The results of similar materials simulation indicated that the height of the fracture zone in different areas of the working face is different due to the influence of a large dip angle. The height of the fracture zone formed in the upper section of the working face is significantly larger than that formed in the lower section of the working face. (3) The numerical calculation suggested that the residual coal pillar of the overlying coal seam has a certain influence on the mining pressure of the 9-301 working face, making the advanced abutment pressure in the rang of 80m close to main gate under the coal pillar more obvious. (4) The field pressure monitoring results demonstrated that the influence range of the advanced abutment pressure close to the upper part of the working face is greater than that close to the lower part of the working face, and the peak point is closer to the mining rib. Affected by the overlying residual coal pillar, the hydraulic support resistance and the peak value of advanced abutment pressure in the lower part of the working face is greater than that in the upper part. Both the initial and periodic pressure intervals of the upper section of the working face are smaller than those of the lower section. The results of this research will provide a scientific basis for reasonable determination of the control measures for the mining pressure.